Belimumab restores Treg/Th17 balance in patients with refractory systemic lupus erythematosus. (October 2018) - Prete, M; Leone, P; Frassanito, M A; Desantis, V; Marasco, C; Cicco, S; Dammacco, F; Vacca, A; Racanelli, V
Belimumab, a specific inhibitor of the soluble B lymphocyte stimulator (BlyS), is the first biological drug approved by the United States Food and Drug Administration for the treatment of patients with active systemic lupus erythematosus (SLE) refractory to standard therapy. Given that an imbalance between regulatory T cells (Treg) and interleukin (IL)-17A-secreting T cells (Th17) has been reported in various autoimmune disorders, we assessed the frequency of both Treg and Th17 peripheral blood populations before and after belimumab administration in 20 patients with active SLE refractory to standard therapy. After six months of treatment, the mean SELENA-SLEDAI score as well as the mean anti-double-stranded DNA antibody titers were significantly decreased. In addition, we observed a significant increase in Treg percentages and a parallel, significant decrease in Th17 percentages, accompanied by significantly reduced serum levels of IL-21. In vitro studies showed that Treg purified from belimumab-treated patients were fully functional and displayed a suppressor function similar to that of Treg purified from healthy donors. Belimumab can restore Treg/Th17 balance in SLE patients with uncontrolled disease activity, and this results in decreased flare rate and reduced glucocorticoid dosage.